Sikap Bahasa Murid Terhadap Bahasa Bali: Studi Kasus di SMKS Kesehatan Bali Medika Denpasar - I Made Sunaryana; I Made Dian Saputra; Ni Gusti Ayu Agung Nerawati; Made Iwan Indrawan Jendra; Ni Gusti Ayu Made Yeni Lestari (Cetta: Jurnal Ilmu Pendidikan, 2026)
Balinese, as an element of Balinese cultural identity, is experiencing symptoms of maintenance shift among the urban younger generation due to the dominance of Indonesian, despite being reinforced through regional language preservation regulations. This condition is of particular concern at the Vocational High School (SMK) level in the health sector in urban areas such as Denpasar, which has not been widely researched and possesses vocational curriculum characteristics different from those of general schools. This study aims to describe the language attitudes of students at SMKS Kesehatan Bali Medika Denpasar toward the Balinese language based on three indicators-namely language loyalty, language pride, and norm of language awareness-while also identifying the factors that influence them. This study employs a descriptive qualitative approach with a case study design. Data were collected through an open-ended questionnaire distributed to 307 students (50% of the population of 614 students), in-depth interviews with 12 selected informants, and field observations, then analyzed qualitatively using an interactive analysis model and validated through source and technique triangulation. The results show that students' language loyalty is relatively low, marked by the dominance of code-mixing and full code-switching to Indonesian in institutional domains; language pride, on the other hand, is relatively high and cuts across ethnic backgrounds, driven by the instrumental value of Balinese in healthcare services; while norm of language awareness regarding Balinese speech levels (sor singgih basa Bali) remains low and largely stems from limited linguistic competence. These findings indicate that students' language attitudes are fragmented across the affective, conative, and cognitive components, so that strengthening positive language attitudes requires strategies that target not only cultural pride but also the habituation of active language use and the contextual reinforcement of Balinese language competence.